Elaborasi Penyusunan Laporan Keuangan Konsolidasi ke Dalam Nilai Syariah Islam - Waluyo, Bambang; Masjono, Ali (Al-Iqtishad: Journal of Islamic Economics, 2012)
This study aimed to obtain a design of the process of preparing the consolidated financial statements associated with shariah values in Islam, especially the value ofÂ  fairness and honesty. The consolidated financial statements are designed to present the result of operations and financial position of the company and its subsidiaries. In the process, it will be clearly seen an effort to avoid injustice and dishonesty, because things are suspected as potentially able to cheat its readers in a way the ellimination of the effect through adjusting entries and elimination. So that, these process will be in accordance with the Quran and the HadithDOI: 10.15408/aiq.v4i2.2104